Analisis Manajemen Pembelajaran Untuk Projek Penguatan Profil Pelajar Pancasila di SMP Bina Taruna Bojongsoang Kabupaten Bandung - Pujawardani, Hani Hadiati; Suganda, A.; Warta, Waska (Jurnal Ilmiah Mandala Education (JIME), 2023)
The purpose of this research is to find out about learning management for Projek Penguatan Profil Pelajar Pancasila as an effort to achieve competency and character values that is in accordance with the Pancasila profile through project-based learning. This research uses a qualitative approach with descriptive methods. The location of this research is at SMP Bina Taruna Bojongsoang Kabupaten Bandung. The subject of this research is management learing in Kurikulum Merdeka. Data collection techniques were carriid out through observation, interviews and documentation studies. The result of the study show that the management of learning for Projek Penguatan profil Pelajar Pancasila through management functions is affective and meaningful.